Fulvestrant in Combination with CDK4/6 Inhibitors for HER2- Metastatic Breast Cancers: Current Perspectives - Iorfida, Monica (Breast Cancer (Dove Med Press), 2020)
The development of CDK 4/6 inhibitors has dramatically changed the therapeutic management of hormone receptor-positive (HR+) and HER2 negative metastatic breast cancer (MBC). In combination with fulvestrant, palbociclib, ribociclib and abemaciclib have each been approved for HR+/HER2- MBC following the results of randomized Phase III studies (PALOMA-3, MONALEESA-3, MONARCH-2) and shown a significant advantage in PFS. Data from clinical trials support the combination with aromatase inhibitors in the first line setting and with fulvestrant in the second line. Each agent is well tolerated, and most of the toxicities observed with this class of drugs are generally easily manageable and free from particular complications. The latest evidence from MONARCH-2 and MONALEESA-3 trials shows benefits in terms of overall survival (OS), suggesting an option of using fulvestrant in combination with CDK 4/6 inhibitors in the first line setting. Additional research is needed to determine optimal treatment sequencing, understand the mechanisms of resistance, and develop novel therapeutic strategies to overcome clinical resistance and further improve the outcomes of patients with HR+/HER- MBC. Key questions in the field include the further impact on progression-free survival, overall survival, and the role of continuing CDK 4/6 blockade beyond progression. The purpose of this review is to describe the clinical relevance of fulvestrant in combination with CDK 4/6 inhibitors in HR+/HER2- MBC patients, as well as to discuss the current controversies and evolving research areas.